The effect of butt jointed dry board in PSSDB wall panel with window opening / Mohd Ghazali Hj Hamzah - Hj Hamzah, Mohd Ghazali (Faculty of Civil Engineering, 2004)
The rapid development of science and technology has led to the introduction of using new constriction techniques and materials in construction industry. One of the innovative composite constructions is profiled steel sheet dry board system. This report presents an experimental investigation on the effect of butt joint in Profiled Steel Sheet Dry Board (PSSDB) system wall panel with window opening. This is a continuation on the studies that have been carried out before using local materials, to get more information on the behavior of the composite materials used. Three samples were prepared with butt joint in the vertical direction on samples of 1320mm x 1000mm x 78mm. The entire sample was tested in one way in-plane action supported at top and bottom edges against lateral displacement and subjected to axial load. Openings in the panels represent typical window openings of sizes 400m x 400mm x 78mm and positioned in the mid section of the panel. Ultimate loads, cracking patterns and lateral displacement of the sample were studied. The parameters measured were ultimate load capacity, displacement and cracking patterns. The ultimate load capacities of the samples were found to be 281kN. 188kN and 296kN. maximum lateral displacements of sample at the ultimate load were —107.1mm. 39.73mm and -38.52mm. It was found that PSSDB with vertical butt joint had no crack from upper part of the sample. It had higher ultimate load capacity compared to that without butt joint.